The Effect Of Current Ratio (CR) And Debt To Asset Ratio (DAR) On Net Profit Margin (NPM) At PT Bekasi Fajar Industrial Estate Tbk Period 2010-2022 - fitriani, aisyah devia (Yayasan Pendidikan Penelitian Pengabdian Al-amsi, 2024)
This study aimed to determine the effect of the current ratio and debt-to-asset ratio on the net profit margin at PT Bekasi Fajar Industrial Estate Tbk. This type of research uses quantitative research methodology with an associative approach. The population was all financial statements at PT Bekasi Fajar Industrial Estate Tbk with samples from 2010 to 2022. Using SPSS version 26 software, this research includes the classical assumption test (normality, multicollinearity, heteroscedasticity, and autocorrelation), multiple linear regression test, determination coefficient test, and hypothesis testing with a significant level of 0.05. Partially, the CR did not affect the NPM. Partially, the DAR did not affect the NPM variable. Simultaneously, both the CR and the DAR, neither of them had influenced the NPM.